HEALTHY FOOD FOR SNACK LOVERS: THE WAY TO SUCCESS IN THE MARKET OF HEALTHY FOOD PRODUCTS - Senturk, H. A.; Cakir, M. (ST PETERSBURG UNIV PRESS, 2023)
Goal: healthy snacks have received increased attention in the food science and technology literature. Nevertheless, studies exploring how factors in the micro and macro market environment can create opportunities and threats for companies in the healthy snacks market are still lacking. The goal of this research is to provide a road map to help companies' strategic directions by examining the micro and macro market environment variables of the healthy snack market. Methodology: we conducted interviews with stakeholders of the healthy snack sector who are knowledgeable and skilled in monitoring and assessing both micro and macro environmental factors. The managers of the firms that are the suppliers, producers, sellers, and distributors of the industry, as well as customers who are aware of healthy food consumption, were interviewed in-depth and semi -structured interviews. Then, content analysis was employed, which uses a set of procedures to make valid inferences from the text. Findings: a correct and accurate strategic orientation starts with a successful analysis process. In this context, the main problems/developments are identified through sectoral structure and sectoral trend analyses, and the opportunities and threats that these will present to companies are revealed. Finally, marketing actions have been proposed to seize these opportunities and overcome the threats. At this point, three important strategic marketing objectives that will guide the strategic orientation of the companies stand out. Originality and contribution of the authors: the paper is the first jointly to examine two sides of the healthy snack market (firm and customer perspective). The study's findings, which were based on in-depth interviews with managers of healthy snacks companies and customers who have high health awareness, provide a road map for firms engaged in strategic marketing.
Keywords: healthy snacks; market environment; sectoral structure; sectoral trends; content analysis; consumer expectations; ORGANIZATIONAL RESEARCH; TOURISM; QUALITY; SYSTEMS; BRAND; Business & Economics